Observing walking with asymmetric treadmill belt speeds induces stronger activation of the action observation network than normal walking - Kitamura, Masaya; Ishikura, Tadao; Kamibayashi, Kiyotaka (Frontiers in Human Neuroscience, 2025)
IntroductionObserving the actions of others activates the action observation network (AON). Although previous studies have reported that motor experience and visual familiarity with an observed action can modulate the AON activity, the response of the AON to the observation of unusual walking patterns remains unclear. Therefore, this study aimed to investigate the brain activity induced by observing walking in a split-belt condition, where the left and right treadmill belt speeds differ.MethodsWe examined the brain activity during the observation of video clips showing normal walking under a tied condition (the same left and right treadmill speeds) as well as walking during the initial and late periods of a split-belt condition using functional magnetic resonance imaging in 19 healthy adults. The step lengths of the actor walking in the video clips were asymmetric during the initial period of the split-belt condition and nearly symmetric during the tied condition and late period of the split-belt condition.Results and discussionObserving the walking video clips activated broad regions of the occipito-temporo-parietal and frontal cortices, irrespective of the clip conditions. The contrasts between the conditions revealed that observing walking in the initial and late periods of the split-belt condition induced stronger activation in a subset of the AON than in the tied condition. These results suggest that observing unusual walking patterns under asymmetric speed condition induces a stronger AON activity than normal walking.